The role of tobacco and alcohol use in the interaction of social determinants of non-communicable diseases in Nepal: a systems perspective - Sudesh Raj Sharma; Anna Matheson; Danielle Lambrick; James Faulkner; David W. Lounsbury; Abhinav Vaidya; Rachel Page (BMC, 2020)
Abstract Background Tobacco and alcohol use are major behavioural risks in developing countries like Nepal, which are contributing to a rapid increase in non-communicable diseases (NCDs). This causal relationship is further complicated by the multi-level social determinants such as socio-political context, socio-economic factors and health systems. The systems approach has potential to facilitate understanding of such complex causal mechanisms. The objective of this paper is to describe the role of tobacco and alcohol use in the interaction of social determinants of NCDs in Nepal. Method The study adopted a qualitative study design guided by the Systemic Intervention methodology. The study involved key informant interviews (n = 63) and focus group discussions (n = 12) at different levels (national, district and/or community) and was informed by the adapted Social Determinants of Health Framework. The data analysis involved case study-based thematic analysis using framework approach and development of causal loop diagrams. The study also involved three sense-making sessions with key stakeholders. Results Three key themes and causal loop diagrams emerged from the data analysis. Widespread availability of tobacco and alcohol products contributed to the use and addiction of tobacco and alcohol. Low focus on primary prevention by health systems and political influence of tobacco and alcohol industries were the major contributors to the problem. Gender and socio-economic status of families/communities were identified as key social determinants of tobacco and alcohol use. Conclusion Tobacco and alcohol use facilitated interaction of the social determinants of NCDs in the context of Nepal. Socio-economic status of families was both driver and outcome of tobacco and alcohol use. Health system actions to prevent NCDs were delayed mainly due to lack of system insights and commercial influence. A multi-sectoral response led by the health system is urgently needed.